2010
DOI: 10.1007/s00417-010-1539-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of doxycycline temperature-sensitive hydrogel on inhibiting the corneal neovascularization induced by BFGF in rats

Abstract: The study results showed that topical DTSH effectively inhibited corneal NV at the ideal concentration of 0.05% and 0.1%. Therefore, topical DTSH could be considered as an alternative treatment for the clinical management of corneal NV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Therefore, bFGF has the potential to promote CNV because the migration and proliferation of vascular endothelial cells is one of the main reasons for angiopoiesis. Past studies have confirmed that bFGF promotes corneal epithelium injury healing while it promotes angiopoiesis [23,24,25,26,27]. Ellenberg et al [28] found that the promotive neovascularization effect of bFGF had a close relationship with that of VEGF, while there was still a distinction between them.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, bFGF has the potential to promote CNV because the migration and proliferation of vascular endothelial cells is one of the main reasons for angiopoiesis. Past studies have confirmed that bFGF promotes corneal epithelium injury healing while it promotes angiopoiesis [23,24,25,26,27]. Ellenberg et al [28] found that the promotive neovascularization effect of bFGF had a close relationship with that of VEGF, while there was still a distinction between them.…”
Section: Discussionmentioning
confidence: 96%
“…30 The photolysis of doxycycline under UVC light (100-280 nm) was investigated by Bolobajev et al It was reported that degradation of doxycycline occurred under various conditions. 31 Although many studies about skin irritation by doxycycline under sunlight have been presented in the literature, 30,32,33 there is no scientific study investigating the effect of doxycycline degradation on initiator reactivity, reaction rate, and conversion during UV-initiated free radical polymerization.…”
Section: 25mentioning
confidence: 99%
“…The length and area of CNV were measured with Image-Pro ® Plus 5.1 (Media Cybernetics Inc, Bethesda, MD), according to a previous report. 28 …”
Section: Quantification Of Cnvmentioning
confidence: 99%
“…28 Briefly, on the sixth postoperative day, the rats were anesthetized again with sodium pentobarbital (50 mg/kg body weight, intraperitoneally) and administered heparin at a dose of 2000 units/kg body weight via tail vein injection to prevent blood clotting. Thirty minutes after infusion, all rats were perfused with 10 mL of Higgins waterproof India ink (Sanford, Oak Brook, IL) through the thoracic aorta to visualize corneal vessels.…”
Section: Quantification Of Cnvmentioning
confidence: 99%